2008
DOI: 10.1002/jctb.1798
|View full text |Cite
|
Sign up to set email alerts
|

Purification of α‐toxin from Clostridium perfringens type A in PEG‐phosphate aqueous two‐phase systems: a factorial study

Abstract: BACKGROUND: Purification of α-toxin produced by Clostridium perfringens type A in aqueous two-phase systems (ATPS) was studied with a full two-level factorial design on two factors (concentrations of 8000 g mol

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…There are frequent reports in the literature regarding recoveries exceeding 100% for enzyme extraction using ATPS, as shown by Cavalcanti et al 25 and Cavalcanti et al. 31 These authors cited enzyme yields of around 230 and 168%, respectively, when the PEG/phosphate ATPS was used for phospholipase C extraction. According to Mayerhoff et al, 32 high values in the recovery of these biomolecules can be explained by the decrease in concentration of potential enzyme inhibitors and activation of enzyme interaction with components of the system, which can favor enzymatic activity.…”
Section: Figure 1 Effects Of Ph On Proteolytic Activitymentioning
confidence: 96%
“…There are frequent reports in the literature regarding recoveries exceeding 100% for enzyme extraction using ATPS, as shown by Cavalcanti et al 25 and Cavalcanti et al. 31 These authors cited enzyme yields of around 230 and 168%, respectively, when the PEG/phosphate ATPS was used for phospholipase C extraction. According to Mayerhoff et al, 32 high values in the recovery of these biomolecules can be explained by the decrease in concentration of potential enzyme inhibitors and activation of enzyme interaction with components of the system, which can favor enzymatic activity.…”
Section: Figure 1 Effects Of Ph On Proteolytic Activitymentioning
confidence: 96%
“…Moreover, the positive interaction among M PEG , C PEG and C PHOS also affected positively K, Y and PF, but had a negative effect on S (Table 3). Cavalcanti et al [56] and Kirsch et al [40] observed that C PEG and C PHOS influenced K, Y and PF. Moreover, pH was also considered to affect K directly [57].…”
Section: Partition Coefficient Activity Yield and Purification Factomentioning
confidence: 98%
“…In addition, the values obtained for the response variables PF and Y were 1.1 and 151%, respectively. In order to evaluate the purification of ␣toxin from Clostridium perfringens type A, Cavalcanti et al [56] used a PEG/phosphate ATPS and obtained the highest values for the PF (5.7) when using a C PEG and C PHOS of 17.5% and 15%, respectively.…”
Section: Partition Coefficient Activity Yield and Purification Factomentioning
confidence: 99%
“…Hence, center-points characterize experimental runs at the center level of each factor range [6,19]. Furthermore, the pure error of the replicated center-point experiments is used to estimate the statistical significance of the calculated values of each factor, and thus evaluate the background variability of the process [6,19,20].…”
Section: Screening Of Significant Factorsmentioning
confidence: 99%